Empirical investigation of digital strategies in online retail - TAN, Yong Chin (Institutional Knowledge at Singapore Management University, 2019)
This dissertation examines digital strategies used by online retailers to engage customers and increase sales. The first essay investigates the impact of offering incentives to recapture lost sales from abandoned online shopping carts (i.e., customers adding items to their carts, but leaving without purchasing). Collaborating with an online fashion retailer, I conducted a randomized field experiment by manipulating the presence of incentives in recovery interventions. Findings reveal that incentives facilitate purchase conversion, but responsiveness to the incentives differs across various customer and cart characteristics. In the second essay, I explore how retailers can leverage Augmented Reality (AR), a technology that helps users visualize how virtual objects fit into their physical reality, to enable customers to try products virtually. Using data from an international cosmetics retailer who incorporated AR in their mobile app, I find that customers who use AR display higher levels of in-app engagement, and are more inclined to explore products and brands they have never purchased before. Furthermore, AR benefits lower-priced products and less-popular brands and could potentially level the playing field for brands or products at the long tail of the product sales distribution. The findings uncovered in these two essays contribute to the literature on digital marketing and retailing, and would benefit retailers who are planning to implement these strategies.